The effect of progressive muscle relaxation therapy on anxiety of hemodialysis patients in Pekanbaru, Indonesia - Anggraini, Silvia Nora; Ayudytha Ezdha, Awaliyah Ulfah; Fitri, Dwi Elka; Ovari, Isna; Lita, Lita; Oktaviani, Nanda (Gaceta Médica de Caracas, 2022)
Introduction: Hemodialysis is a renal replacement therapy used by patients with chronic kidney failure. Psychological problems that hemodialysis patients often experience are anxiety. Anxiety among hemodialysis patients can be overcome by relaxation, one of which is progressive muscle relaxation. This study aimed to determine the effect of progressive muscle relaxation therapy on the anxiety level of hemodialysis patients.